Hepatic histologic findings in a case of MEGDHEL syndrome due to SERAC1 deficiency. Issue 9 (4th July 2022) - Yuen, Lisa; Sahai, Inderneel; O'Grady, Lauren; Selig, Martin; Walker, Melissa Anne; Shah, Uzma; Misdraji, Joseph
Abstract: MEGD(H)EL syndrome is a rare autosomal recessive disorder caused by mutations in SERAC1, a protein necessary for phosphatidylglycerol remodeling. It is characterized by 3‐methylglutaconic aciduria, deafness‐dystonia, (hepatopathy), encephalopathy, and Leigh‐like syndrome, but has a wide spectrum of severity. Here, we present a case of a child with MEGD(H)EL syndrome with infantile hepatopathy, neurodevelopmental delays, characteristic biochemical abnormalities, and biallelic novel SERAC1 mutations: (1) deletion of (at least) exons 2–4, pathogenic; and (2) c.1601A>T (p.H534L), likely pathogenic. Her initial clinical presentation was notable for persistently elevated transaminases, speech delay, delayed motor milestones, and sensorineural hearing loss. However, her verbal and motor development has progressively improved and now, at 4 years of age, she has only speech and mild gross motor delays as compared to her unaffected peers and is exceeding clinical expectations. The histologic features of a liver biopsy are described, which has not previously been published in detail for this syndrome. Hepatocytes showed granular cytoplasm and fine intracytoplasmic lipid droplets. The ultrastructural findings included abnormal circular mitochondrial cristae. These findings are consistent with a mitochondrial disorder.